The Practicality of Electronic Physics Module Based on Scientific Approach on Fluid Materials - Zakirman Zakirman; Chichi Rahayu; Wienda Gusta (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
The purpose of this study is to describe the level of practicality of the electronic physics module based on a scientific approach to fluid materials. Research and development using a 4D model consisting of the stages of defining, designing, developing, and disseminating. The practicality test is carried out after the definition and design stages are completed. The research instrument is an observation sheet on the implementation of lesson plans, teacher response questionnaires, student response questionnaires, and the respondents are teachers and students of class XI MIA in one of the SMAN in Padang City. The method used is descriptive statistics to get the average value and percentage. An electronic physics module based on a scientific approach is said to be practical if the practitioner's assessment states that the module can be applied. Based on the teacher's response, the average percentage of 89.28% met the very practical category and the student's response was 78, 45% met the practical category. Overall, the average percentage of the practicality of the electronic physics module based on this scientific approach is 83.86% in the very practical category. This shows that the electronic physics module based on a scientific approach is easy to use and useful for teachers and students.